Investment decision in crisis: The alternative view of escalation of commitment in determining investment performance - Harris Turino Kurniawan; Adhi Setyo Santoso (Cogent Business & Management)
This research attempts to apply Image Theory to examine whether the tendency to continue the initial strategy or maintain the status quo known as escalation of commitment (EoC) from institutional investors leads to positive investment performance in unstable real environmental conditions with certain changing trends. In the equity market, investors are always faced with the option of maintaining their existing portfolio (initial strategy) or modifying it (generate emergent strategy) to increase assets as the goal. However, they have a tendency to EoC. Based on this situation, the authors conduct a quantitative study with covariance-based structural equation models (CB-SEM) approach one of the fund management industry in the Indonesian equity market during bearish conditions in the midst of the 2008 global economic crisis and bullish conditions during the crisis recovery as the background. This study shows that EoC is not always associated with more negative performance because it can result in more positive performance in high image compatibility state.